Planting Trees as City Lungs in Mabar Village, North Sumatra - Siregar, Ameilia Zuliyanti; Derrick, Neilson; Annisa; Darma, Miya Meilita; Zulfa, Nisrina Khairani; Panggabean, Judika (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The implementation of community service activities carried out by the KKN R-16 group was carried out on July 14, 2021 in Mabar Village, Medan Deli by planting three varieties of trees, namely guava (Syzygium aqueum), mango (Mangifera indica) and rambutan (Nephelium lappaceum). 36 plants along the green line of Mabar Village. The method of implementing KKN is carried out offline or offline, namely socialization, training and tree planting and distributing questionnaires to 30 respondents. Data from the calculated questionnaire showed that 24 respondents strongly agreed to plant trees in Mabar Village. In the implementation of the activities carried out, the people of Mabar Village enthusiastically welcomed and supported the KKN activities of planting trees as the lungs of the city. It is hoped that this plant in the future can become a source of oxygen and reduce flooding in the rainy season.